Qualitative Analysis of Barriers and Facilitators to Cancer Screening in Low-Income Communities - Singer, Michael E; Bastholm, Mathias; Qiu, Haixin (Health Nexus, 2024)
This study aimed to explore the barriers and facilitators to cancer screening among individuals in low-income communities. By understanding these factors, the research sought to provide insights that could inform interventions designed to increase screening rates and reduce cancer-related health disparities in these populations. A qualitative research design was employed, utilizing semi-structured interviews to collect data from 24 participants residing in low-income communities. The participants were recruited through community centers, local clinics, and public health organizations. Data collection continued until theoretical saturation was achieved. The interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo software. Thematic analysis was conducted to identify key themes and patterns within the data. The study identified several barriers to cancer screening, including lack of awareness, financial constraints, fear and stigma, accessibility issues, and negative past experiences with healthcare providers. Facilitators included community support, education and awareness programs, accessibility improvements, financial assistance, positive healthcare experiences, and culturally competent care. Participants highlighted the importance of social support networks and the role of community health workers in encouraging screening participation. Financial aid and logistical improvements were also crucial in enabling access to screening services. Positive interactions with healthcare providers and culturally sensitive care emerged as significant factors in promoting screening uptake. Addressing the barriers and leveraging the facilitators identified in this study is essential for improving cancer screening rates in low-income communities. Interventions should focus on comprehensive education and awareness campaigns, financial assistance programs, and accessibility improvements. Training healthcare providers in cultural competence and fostering positive healthcare experiences can further enhance screening participation. By implementing these strategies, healthcare systems can reduce cancer-related health disparities and improve early detection in underserved populations.